Soil Organic Carbon Stocks as Influenced by Forest Management and Socio-Economic Characteristics of Community Forest User Groups in Three Districts of Central Nepal - Sitaula, Bishal K.; Raut, Nani; Dahal, Nirmal Mani; Bhatt, Yagya Raj; Bajracharya, Roshan Man; Lal, Rattan (Indian Forester, 2019)
This paper examines the forest-based livelihood strategy of the forest user groups and the prospects and potential benefits of soil carbon sequestration through REDD (Reducing Emissions from Deforestation and Forest Degradation) program in three districts of Central Nepal, namely Chitwan, Gorkha and Rasuwa. The objectives were to assess forest-based livelihood strategy and soil organic carbon (SOC) stocks in the community forest and agro-forest systems. Data were collected through a household survey, focus group discussions and laboratory experiments. Findings from this study showed that crop productivity has increased after establishment of community forest. Community forest users groups (CFUGs) use of fuelwood and leaf litter was higher than other non-timber forest products (NTFPs). The CFUGs of community forest managed by women (Chelibeti and Laxmimahila) have used biogas as an alternative energy source compared with men-managed community forest. Farmers had participated in various training courses including vegetable farming, livestock management and forest inventory. The study revealed that forest soil has a high potential to sequester carbon. The highest value of SOC stock (374 Mg/ha) was recorded in higher elevation forestland of Rasuwa district followed by Improved Agroforestry (IA) (244 Mg/ha) and Traditional Agroforestry (TA) (210 Mg/ha). The comparison of SOC stock within the community forests and agroforestry with other forests, showed that wellmanaged forests had two to three times as much SOC stock as degraded forests. The estimation of potential SOC gained indicated the likely future benefits of enhancing SOC stock through community forests and agroforestry.